Hubungan Kualitas Air Sungai dengan Keluhan Kesehatan Di Desa Sitio-Tio Kota Pematang Siantar - Linda Hernike Napitupulu; Junita Magdalena Simanjuntak; Ani Deswita Chaniago; Endang Mariati (Pusat Riset dan Inovasi Nasional, 2025)
Water is an important factor in fulfilling the vital needs of living creatures, including drinking water or other household needs. The water used must be free from germs and not contain toxic materials. The results of research by researchers found that 95 people in the Sitio-tio village had cases of 14 people experiencing serious health complaints. Objectives; to determine the relationship between river water quality and health complaints in Sitio-tio village, Siantar Sitalasari sub-district, Pematang Siantar city. This research is an analytical survey with a design using a cross sectional approach, proportional random sampling method. The population of this study was all heads of families in Sitio-tio village, Siantar Sitalasari subdistrict, a population of 95 heads of families with 6 river water samples. Data analysis used bivariate analysis with the chi-square statistical test. The results of the bivariate analysis show that the p value for the variable river water quality and health complaints (p = 0.016) is <0.05, there is a relationship between river water quality and health complaints. The conclusion of this research is that there is a relationship between river water quality and health complaints in Sitio-Tio village, Siantar Sitalasari sub-district, Pematang Siantar city. Recommended to the Sitio-tio village community to maintain the cleanliness of the Sitio-tio river water, reduce careless use of river water and not throw rubbish in the Sitio-tio river flow which pollutes the river so that there is less risk of the Sitio-tio community getting diseases caused by dirty river water.